Racism towards Japanese-American In Isabel Allende’s The Japanese Lover (LITERA KULTURA : Journal of Literary and Cultural Studies, 2018)
Abstrak Rasisme telah menjadi konflik utama di Amerika. Namun, masalah rasisme tidak hanya terjadi pada orang-orang berkulit hitam, tetapi juga terjadi pada orang Jepang-Amerika. Orang Jepang-Amerika adalah para imigran yang datang dari Jepang ke Amerika untuk menetap dan tinggal di Amerika. Dengan berlatar belakangkan sejarah perang dunia II, Allende mencoba menggambarkan bagaimana rasisme terjadi pada orang-orang Jepang-Amerika dalam novelnya The Japanese Lover. Orang imigran Jepang dan juga keturunannya diperlakukan secara berbeda dan tidak baik, terutama saat mereka tinggal dalam kamp pengasingan. Maka dari itu, studi ini bertujuan untuk menemukan bagaimana rasisme terjadi dan efeknya pada orang-orang Jepang-Amerika itu sendiri. Rasisme juga memberikan pengaruh terhadap kehidupan para tokoh yakni seperti perasaan khawatir, rendah diri dan depresi. Kata kunci: Rasisme, PerangDunia II, Orang Jepang-Amerika dan kamp pengasingan. Abstract Racism has been one of the major conflict social in America. Unfortunately, problems of racism are not only against black people but also Asian people especially Japanese-American. Japanese-American is Japanese immigrants who lived in America for years till the generations afterwards. By using history of World War II, Allende attempted to illustrate who racism happened to Japanese-American in her novel The Japanese Lover. Both of Japanese immigrants or their descendants were treated arbitrarily particularly when they were lived in internment camp. Therefore this study proposed to discover ho racist acts occur and effects of racism towards Japanese-American by using the novel The Japanese Lover as the source of this study. Thereafter, racism gives impacts on the characters life such as feeling of anxiety, low self-esteem and depression. Keyords: Racism, World War II, Japanese-American and internment camp